THE SIGNALS OF BEING OPPRESSED AND THE OPPRESSORS IN THE TEACHERS’ PERCEPTION OF EDUCATION. A CASE STUDY OF VIETNAM FROM CRITICAL THEORIES - Phan Thi Tuyet Van; Nguyen Duy Khang (Society Register)
In light of Freire Today, this paper aims to present the results from a case study in Vietnam about the teachers’ perception of education with the recognized signals of being oppressed and the oppressors in their teaching. This study was conducted to clarify the problems preventing education to be developed in this context with the participants from 3 provinces in the Mekong Delta of Vietnam. The qualitative data was collected through using a mixture of 7 interviews and 10 opened-question surveys due to the geographical difficulties. The data collection was framed by using the Padilla’s (1994) techniques of unfolding matrix for data analysis. The findings show that the authoritarian education remains unchanged or slowly transformed with the signals of the teachers as both the oppressors to their learners and the oppressed in their working system. The findings would be meaningful during the ways to figure out the real challenges of current Vietnamese educational system in which critical theories could be considered as one of the possible solutions.